(Re)Building a feeling of belonging in complex emergencies: Challenges and opportunities in the education of refugee children through the experiences of Afghans in Pakistan - Dicum, Julia (Ethnologies, 2005)
AbstractIn an effort to contribute to the development of the emerging field of studies related to complex emergencies, this article seeks to define recent trends in curriculum studies and research methodology in comparative and international education (CIE) and will suggest crucial areas where CIE and curriculum studies contribute to theory building for a qualitative praxis of implementing learning environments in complex emergency contexts. It goes on to test the emerging sense of a critical learning theory for survival against the case study of Afghan refugee education in south-west Pakistan during the Taliban era. This represents an attempt by emergency educationists to move away from solely focusing on the practical aspects of their field towards thinking more strategically and deeply about the nature of the field itself and suggesting early directions that theory development might usefully take. The paper draws on the author’s firsthand experiences of managing refugee education programmes, as well as publicly available policy documents, field reports, and the strong theoretical traditions within curriculum studies, thereby highlighting the need for rigorously developing a deeper understanding of education for survival in complex emergency environments.